Śrīmadbhāgavata purāṇa pariśīlanamu - Nāgasiddāreḍḍi, Ḍi., 1930- (T.T.D. religious publications series ;, 1980)
Study of the Bhāgavatapurāṇa, with reference to its Telugu verse rendering, Śrīmahābhāgavatamu, by Pōtana, 15th century Telugu poet.